Pelatihan Manajemen Arsip Dinamis di Kecamatan 2 X 11 Enam Lingkung Kabupaten Padang Pariaman Sumatera Barat - Armida, Armida; Susanti, Dessi; Sarianti, Rini (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
The purpose of this community activity is 1) increasing knowledge of administrative officers in District 2 x 11 Enam Lingkung concerning the creation and reception of the archives, distribution, use, as well as depreciation of the archive, 2) realizing the sub-district office employee are capable of doing the handling or management of archieves. Implementation of training using a variety of methods and approaches, namely as follows: 1) methods of lectures and discussion; a to deliver the theoretical material about the program handling of archives, namely creation and acceptance Archive, distribution, use, as well as depreciation of the archive, 2) method of training and individual guidance related to the management and activities of archives rearrangement, 3) method resitasi or administering the tasks performed to find out so far where the ability of participants in the care of the archives. The result of the activities of this devotion is 1) 90% of the participants understand the concept of archives, 2) 90% of the participants was able to do the handling or management of archives.